The EFFECT OF OPERATIONAL AUDITS THROUGH PRODUCTION FUNCTIONS ON CONSUMER SATISFACTION - M. Sigit Adi Nugraha; Ridwan Ridwan (Journal of Accounting Inaba, 2022)
This research is descriptive research with a quantitative approach carried out on a CV. Baraka Outstanding Workshop. This study aims to determine the presence or absence of the influence of operational audits through the production function on consumer satisfaction. The data collection method in this study is a questionnaire, and the sampling technique used is a census. The population that was the object of the study was employees and customers with a sample of 46 employees and 46 customers. Hypothesis testing was carried out by linear regression analysis for hypotheses 1, 2, 3, path analysis, and Sobel test for hypothesis 4 through the IBM SPSS Statistics V.25 program. Based on the results of the study with a significance level of 5%, conclusions were obtained: Operational Audit has a positive and significant effect on satisfaction with an influence of 95.4%, Operational Audit has a positive and significant impact on the Production Function with an influence of 48.3%, the Production Function has a positive and significant impact on consumer satisfaction with an influence of 52.9%, Operational Audit through the production function has a positive and significant effect on satisfaction consumers 79.5% influence and the rest influenced by other unknown factors which are 20.5%.